Flexible bronchoscopy and cryoextraction for critical airway obstruction caused by an endobronchial angioleiomyoma - Chatterji, Sumit (Respirol Case Rep, 2019)
Angioleiomyomas are rare airway tumours with potential to cause central airway obstruction or haemoptysis. Methods described to manage them include surgical resection, or rigid bronchoscopy and thermal ablation techniques. We describe a case presenting with central airway obstruction, safely and effectively treated with cryoextraction of the tumour using flexible bronchoscopy.